Ethnopedagogy-Based Literacy E-Modules in Pancasila Education Subject - Hadian, Nila Sekardhani; Tirtoni , Feri (Lectura : Jurnal Pendidikan, 2024)
This article examines the level of validity and effectiveness in the use of literacy e-module teaching materials with ethnopedagogy as a learning approach in Pancasila Education subjects. The research method chosen is Research & Development with the ADDIE development model. The subjects in this study were material and learning media experts and e-module product trials on students. E-module teaching materials were used as the object of research. Data collection used interview sheets, teacher and learner needs analysis sheets, pre-test and post-test questionnaires, and respondent questionnaires. The data analysis used descriptive qualitative and descriptive quantitative methods. The results of this study state that in the product validation test by experts obtained a result of 1 using the Gregory test calculation and included in the category with Very High Validity. For the Learner trial, it obtained a score of 87.68% with very good criteria. Based on the results of the results of working on the pre-test and post-test questions of students with the N-Gain Score test, a value of 75.43% was obtained, with the N-Gain effectiveness category being "quite effective". Then, for the acquisition of the N-Gain Score value of 0.56 with the criteria for increasing the learning outcomes of "Moderate" Learners. Overall, the validation results can prove that ethnopedagogy-based literacy e-module teaching materials in Pancasila Education subjects for grade IV at SD Negeri Keret are very feasible to be applied in learning.